Kognisi Sosial Dalam Narasi Terstruktur, Sistematis, dan Masif (TSM) di Persidangan Pemilu Pilpres 2019 Melalui Uji Linguistik Forensik - Romdlon, Atiq Mohammad; Fidiyanti, Murni; Syaikhu, Ahmad; Rosyidi, Zudan (Dialektika: Jurnal Bahasa, Sastra, dan Pendidikan Bahasa dan Sastra Indonesia, 2022)
This study analyzes social cognition on TSM (structured, systematic, and massive) narrative created by the lawyers of the presidential election pair (paslon) 2 during the 2019 presidential election dispute hearing at the Constitutional Court (MK). The representation of social cognition is in the form of knowledge which includes the principles of "substantive justice". The research method used refers to linguistic forensics based on Teun A. van Dijk's Critical Discourse Analysis (AWK) approach. The data were transcripts of court conversations made by the Constitutional Court (MK). This study found that the social cognition of the team of lawyers for the 2nd presidential candidate pair is a representation of the principle of substantive justice. This principle consists of four pieces of knowledge, namely the rationality of substantive courts, honesty and abuse of power by government officials, the objectivity of the constitutional court, the impartiality of the government and election organizers. This principle was used by the team of lawyers for the presidential election pair 2 to encourage MK judges not only to recount the votes but also to investigate TSM violations that were allegedly committed by the presidential election candidate pair 1.